Perbedaan hasil belajar fisika menggunakan LKS berorientasi model pembelajaran kooperatif tipe TTW dengan tipe TAI pada materi gerak parabola dan gerak melingkar pada siswa kelas X SMAN 8 Padang - Fakhruddin Arrazzi; Hidayati Hidayati (PILLAR OF PHYSICS EDUCATION, 2019)
This study discusses the use of student worksheet (LKS) oriented by Think-Talk-Write (TTW) cooperative learning model with Team Assisted Individualization (TAI) type on parabolic and circular motion material on physics learning outcomes from class X students of SMAN 8 Padang. The aim of the study is to investigate differences in physics learning outcomes by using this LKS. The type of this research is a pseudo-experimental study using the Randomized Control-Group Posttest Only design. The population of this study was the class X students of SMAN 8 Padang in the first semester who were registered in the 2018/2019 academic year. The sampling technique used purposive sampling. Based on data analysis, it was found that the data on students' physics learning outcomes were as follows. First, for the attitude competencies, the average value of students in the experimental class 1 and 2 were 77.34 and 88.38 respectively. Second, for knowledge competencies, the average value of students in the experimental class 1 and 2 were 41.32 and 43.24, respectively. Third, for skills competency, the average values of students in the experimental class 1 and 2 are 76.14 and 79.29, respectively. The hypothesis test result showed differences that mean physics learning outcomes of students using LKS oriented cooperative learning model TTW type with TAI type on parabolic motion material and circular motion in class X SMAN 8 Padang only in the attitude competence at a significant level of 0.05.